Support for green laser Nd-YAG and red laser He-Ne Composition and differentiation Kalas Wild plant Kalangum Silybum marianum L. - Alaa Raad Meshaal Meshaal; shefae Saleh (College of Education for Pure Sciences, 2019)
The present  study includes identification the effect of green laser (Nd-YAG) of wavelength 532nm, power 87mw and red laser (He-Ne) of 650nm wavelength,power5mw.at exposing period 10,15,20,25,30 minutes on callus initiation , protein content and regeneration of  Silybum marianum L.plants the effect of  laser was clear by decreasing the time needed for callus induction, and to increasing the fresh weights of  callus. The results showed  that there are an increase in the protein contents reached to 0.570,0.707 µg/gm  of leave's and cotyledonary leave's callus   respectively at 25 min. exposing time to  Nd-YAG laser.The results proved the suitability of 30 min. exposing period  for hypocotyls  and roots since the protein content was 0.750 and 0.410 µg/gm. Moreover,   red  laser (He-Ne) has possessed a positive effect since the highest protein content  of  leave's, hypocotyls  and root callus was 0.481 ,0.548 and 0.484 µg/gm. respectively at 30min. exposing time.while that of cotyledonary leaves was 0.537 µg/ gm at  25min. exposing period.